Why do UAE Courts annul Final Arbitral Awards which are issued in the UAE? - Al Marzooqi, Mohamed (2013)
Arbitration is one method to resolve disputes out of different methods available in the construction industry. The UAE law through the Civil Procedure Code provides some articles which governs the arbitration. The requested outcome of the arbitration is a reward which could be recognized and then be enforced by courts. Annulment is one of the main risks for refusing to recognize an arbitral award. The dissertation will focus on the challenging grounds to annul arbitral awards which are issued in the UAE and finding out what were the main reasons to annul the arbitral awards by the courts. The best comprehensive way of finding the answers to this question is through studying all related judgments from the main courts in the UAE since the issue of law in 1992 until the date of starting this dissertation. Using practical experience in arbitration both ad hoc and institutional and being a witness expert in all UAE courts since 2004, in addition to utilizing a computer programme, reached to some important outcomes and conclusions that will help all parties involved in arbitration including arbitrators, arbitration centers, courts, legislative authorities and legal firms.